ROLE OF TALENT MANAGEMENT PROGRAMMES ON EMPLOYEE PERFORMANCE IN PROFESSIONAL CONSULTANCY SERVICES FIRMS IN KENYA - Wamwangi, Francis Maina; Kagiri, Dr. Assumptah (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of this study was to establish the influence of talent management programmes on employee performance in professional consultancy services firms with focus on Deloitte. Methodology: Descriptive study design was applied. The population targeted the 218 employees at Deloitte East Africa that were stationed in Nairobi. Stratified random sampling was applied to select a sample of 141. A questionnaire was utilized to collect primary data. Statistical Package for the Social Sciences (SPSS) was used in analysis and descriptive, correlation and regressions analysis were conducted. Results: The study results showed that talent acquisition was a significant positive predictor of employee performance. Study findings also established that talent development was a significant positive predictor of employee performance. Moreover, talent retention had a significant positive effect on employee performance. Unique Contribution to Theory, Practice and Policy: The study recommended that Deloitte East Africa should ensure that it has enough digital presence to ensure that they forge connections with candidates and strengthen the employment brand. Deloitte East Africa should have a director of talent and development whose responsibilities should be to lead the design, implementation, and evaluation of talent development and management programs. Lastly, since all employees are different with unique goals and desires, Deloitte East Africa should have unique talent retention practices that will appeal to the diverse workforce.